2017
DOI: 10.4172/2155-6113.1000741
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Self-Perceived Risk of Cervical Cancer among Women Living in Namuwongo, an Informal Settlement in Kampala, Uganda

Abstract: Background: Cervical cancer remains one of the leading causes of morbidity and mortality among women of reproductive age in sub Saharan Africa. However there is limited data on the level of awareness and perceived risk among women in peri urban slums of which most of the occupants are mainly women of reproductive age. Methods:We carried out a population based cross-sectional study in Namuwongo, a peri urban slum in Kampala in 2016. Data was collected using a pretested interviewer administered questionnaire, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
1
4
1
Order By: Relevance
“…In a cross-sectional study on women's knowledge and attitudes about cervical cancer prevention in Eastern Uganda, Mukama et al (2017) found that up to 85% of participants knew at least one symptom or indicator of cervical cancer. Contrary to this result, two other researches (Ajambo et al, 2017& Tesfaye et al, 2019 found that participants in Uganda and Ethiopia had insufficient awareness about cervical cancer and its causes. According to Mahumud1 et al, 2020, women's knowledge and use of CCS services is unequally distributed in Low-and Middle-Income Countries, with socioeconomically poor women in the majority of countries.…”
Section: Literature Reviewcontrasting
confidence: 83%
See 3 more Smart Citations
“…In a cross-sectional study on women's knowledge and attitudes about cervical cancer prevention in Eastern Uganda, Mukama et al (2017) found that up to 85% of participants knew at least one symptom or indicator of cervical cancer. Contrary to this result, two other researches (Ajambo et al, 2017& Tesfaye et al, 2019 found that participants in Uganda and Ethiopia had insufficient awareness about cervical cancer and its causes. According to Mahumud1 et al, 2020, women's knowledge and use of CCS services is unequally distributed in Low-and Middle-Income Countries, with socioeconomically poor women in the majority of countries.…”
Section: Literature Reviewcontrasting
confidence: 83%
“…In a study done by Tsegaye et al, 2018 in Ethiopia, more than half of participants had a positive attitude towards CCS. Studies done by Tapera et al, 2017 in Botswana andAjambo et al, 2017 in Uganda found that majority of participants felt at risk of developing cervical cancer. Similarly, in other studies done by & Ajambo et al, (2017), in Uganda and western Kenya respectively, majority of participants who had ever heard of CCS felt at risk for CC although their specific knowledge was generally low.…”
Section: Literature Reviewmentioning
confidence: 96%
See 2 more Smart Citations
“…In Uganda, cervical cancer annual mortality is alarming at 2275 death (27.2 deaths per 100,000 women) [60]. There is a high level of community awareness about cervical cancer [61][62][63]. However, for the community to participate in effective advocacy, they need to be mobilised so that they can campaign for better services.…”
Section: Discussionmentioning
confidence: 99%